One-Pot Hydrothermal Synthesis of NiFe2O4 Immobilized on Reduced Graphene Oxide: Characterization and Photocatalytic Application for Environmental Remediation - Daranadale, Snehal V.; Murade, Rupali D.; Waghmare, Amit S.; Hase, Dinesh P.; Murade, Vaishali D. (Asian Journal of Chemistry, 2026)
Wastewater generated by the textile industry contains substantial amounts of organic pollutants, particularly synthetic dyes, which pose serious risks to human health and aquatic ecosystems. The removal of these contaminants from water bodies is essential, necessitating the development of cost-effective and efficient treatment strategies. The present study focuses on the development of cost-effective nanostructured materials for dye removal from wastewater and antibacterial activity against both Gram-positive and Gram-negative bacteria. A NiFe2O4/rGO heterojunction was synthesized via a one-pot hydrothermal method and characterized to assess its structure, morphology and optical properties. The synthesized material was evaluated for its catalytic removal of methylene blue (MB) and malachite green (MG) dyes and NiFe2O4/rGO (10%) showed 98.01% and 98.53% removal of MB and MG dyes, respectively, in 120 min. The catalytic removal rate of NiFe2O4/rGO (10%) heterojunction was much faster (98.01%; 98.53%) than the pure NiFe2O4 (73.43%; 73.16%) under visible light illumination. The substantial stability and reusability of the heterojunction were assessed through repeated photocatalytic degradation cycles. Its antibacterial activity was evaluated against the selected multidrug-resistant microorganisms, with NiFe2O4/rGO exhibiting significant zones of inhibition against both bacterial strains. These findings support the potential application of NiFe2O4/rGO in wastewater treatment, particularly for the removal of organic dyes and bacterial contaminants.